On the theories of angular distribution and correlation of beta and gamma radiation - Groot, S.R. de (Elsevier, 1952)
In both phenomena of angular distribution and angular correlation, one has nuclear radiation from ensembles of nuclei with an unequal population of the magnetic sub-levels. This population is described by appropriate “orientation parameters”. On this basis the theories of the directional as well as the polarization aspects of angular distribution and correlation are reviewed in this paper. Special attention is paid to the quantum-mechanical description of polarization by means of statistical matrix elements and Stokes parameters. Results and examples are considered especially of the distribution of gamma and beta rays, and the correlation of gamma-gamma, beta-gamma, and beta-neutrino radiation.
Keywords: Natuur- en Sterrenkunde